Преодоление: Записки психиатра / Л. Н. Земсков - Земсков Леопольд Николаевич (Лениздат, 1991)
Экземпляры: аб. (1991) / Инвентарный номер: 33875 / Цена: / Сис.шифр: 56.14 / Авт.знак: З-55 / ГРНТИ: 76.29.52 / ББК: 56.14